Analysis of quantitative research on consumer behavior and satiation in the Web of Science’s database - Cervi, Cleber; Kieling, Ana Paula; Steil, Andrea Valéria; Dandolini, Gertrudes Aparecida; Souza, João Artur (Revista de Administração da UFSM, 2015)
This article aims to map quantitative research related to consumer behavior and satiation through the founded resources in the ISI Web of Science’s database. The systematic review founded 731 studies related to satiation in 28 different journals. From this sample, it was aimed to study the quantitative research articles related to consumer behavior and satiation in its content. Through analysis, it was noted experimental research and modeling as the main methods applied in this field. Another interesting fact is that the psychological aspects, especially the cognitive aspects, have received many attention in research related to satiation and consumer behavior. Finally, it has emphasized that investigate the influence of emotions and specific cognitive factors on satiation has promising potential for future research concerning the analyzed subject.